2019
DOI: 10.1080/10810730.2019.1583701
|View full text |Cite
|
Sign up to set email alerts
|

“I was Right about Vaccination”: Confirmation Bias and Health Literacy in Online Health Information Seeking

Abstract: When looking for health information, many people turn to the Internet. Searching for online health information (OHI), however, also involves the risk of confirmation bias by means of selective exposure to information that confirms one's existing beliefs and a biased evaluation of this information. This study tests whether biased selection and biased evaluation of OHI occur in the context of early-childhood vaccination and whether people's health literacy (HL) level either prevents or facilitates these processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(125 citation statements)
references
References 34 publications
1
107
1
3
Order By: Relevance
“…11 Further analysis of AI websites and social media is needed to determine the full extent of these and other biases. 87 Second, the evidence for some of the individual nudge approaches has also been challenged; for example, a failure to replicate some of the key studies of priming, 91 though this does not invalidate the fact that the industry uses approaches based on priming, even if the evidence is flawed. Finally, we cannot be certain that the AI examples that we cite are intentional.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…11 Further analysis of AI websites and social media is needed to determine the full extent of these and other biases. 87 Second, the evidence for some of the individual nudge approaches has also been challenged; for example, a failure to replicate some of the key studies of priming, 91 though this does not invalidate the fact that the industry uses approaches based on priming, even if the evidence is flawed. Finally, we cannot be certain that the AI examples that we cite are intentional.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…The role of confirmation bias has already been explored in health information sampling research suggesting that it may significantly affect how information is collected. In recent research, Meppelink et al [ 56 ] investigated the role of confirmation bias in information seeking with respect to early-childhood vaccination and found that a priori vaccination beliefs biased selection of online health information—people predominantly selected information that was consistent with their existing beliefs (ie, selective exposure) [ 57 ]. The significant effect of sampling strategy index on causal estimations showed that, in addition, a partial selection of information in which belief-supporting evidence is overrepresented may be related to damaged causal estimation (note that the correlational nature of our design does not allow us to discriminate whether the biased searching caused the estimates to be biased, or whether a stronger initial belief about the causal relationship might have biased the sampling strategy, strengthening the initial belief).…”
Section: Discussionmentioning
confidence: 99%
“…Social media has a major impact on the way that people interact and exchange information, and this is also the case in the antivaccination debate [ 53 ]. Since information on the internet may influence people’s behavior regarding vaccination, it is important that facts are shared; yet, the social media platforms that enable individual users to find and share information easily can have two side effects on vaccination decision: they can lead people to get vaccinated [ 54 ], but antivaccination movements also can be strengthened [ 55 , 56 ]. Thus, it is relevant to observe the vaccination debate on social media and to examine how antivaccination movements proceed [ 57 ].…”
Section: Related Workmentioning
confidence: 99%